-k+2=-2k-2-4

Simple and best practice solution for -k+2=-2k-2-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -k+2=-2k-2-4 equation:


Simplifying
-1k + 2 = -2k + -2 + -4

Reorder the terms:
2 + -1k = -2k + -2 + -4

Reorder the terms:
2 + -1k = -2 + -4 + -2k

Combine like terms: -2 + -4 = -6
2 + -1k = -6 + -2k

Solving
2 + -1k = -6 + -2k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '2k' to each side of the equation.
2 + -1k + 2k = -6 + -2k + 2k

Combine like terms: -1k + 2k = 1k
2 + 1k = -6 + -2k + 2k

Combine like terms: -2k + 2k = 0
2 + 1k = -6 + 0
2 + 1k = -6

Add '-2' to each side of the equation.
2 + -2 + 1k = -6 + -2

Combine like terms: 2 + -2 = 0
0 + 1k = -6 + -2
1k = -6 + -2

Combine like terms: -6 + -2 = -8
1k = -8

Divide each side by '1'.
k = -8

Simplifying
k = -8

See similar equations:

| 9(b+7)=9(b-5) | | 1(23)(-18)(2)= | | Y-39=-39 | | 8k-4k-8= | | (1)(23)(-18)(2)= | | 2-6j+8j=-2j-10 | | 8y-8-3y=12y-6 | | -5(r+9)=-53 | | 9(o+2)=3(o-2) | | 5.7+1.8n=0.84 | | 5d=9d-20 | | 15k^2-8=-2k | | 8-6x+x=2-3x | | 9-5z=12-6z+7 | | 83-x=93-2x | | .8(x+4)-.3x=1.7 | | n*2-12=34 | | 3y-6y^2=0 | | 25=-7(x+5)+5x | | 5x+8y=6e | | 3x+5=350 | | 8=-4x+x+8 | | ln*(x+3)+ln*9=1 | | 8(x+9)=80 | | (-34)+50+50= | | 85-3x=4 | | -5n=13-13m | | 6x-2y=4x+6y | | y=2x^2-7x-30 | | 8x^2=4x+14 | | 6a+12=6a-12 | | p=8p+p |

Equations solver categories